Безфакторный поли (dT)-зависимый синтез олигофенилаланина на 70S рибосомах Escherichia coli - Солдаткин, К.А.; Потапов, А.П.; Ельская, А.В. (Биополимеры и клетка, 1987)
Показано, что в условиях бесфакторного поли(dT)-зависимого связывания Phe-тРНКᴾʰᵉ с 70S рибосомами Е. coli имеет место синтез олигофенилаланинов как при низких (2°С), так и при высоких (37 °С) температурах. Поли(U) в этих же условиях не транслируется. Антибиотик неомицин ингибирует бесфакторную трансляцию поли(dТ) на стадии транслокации и не влияет на взаимодействие Phe-тPHKᴾʰᵉ с поли(U)-программированными рибосомами (связывание и транспептидацию). Показано, що за умов безфакторного полі (dT)-залежного зв’язування Phe-тРНКᴾʰᵉ з 70S рибосомами Е. coli має місце синтез олігофенілаланінів як за низьких (2 °С), так і за високих (37 °С) температур. Полі (U) за цих же умов не транслюється. Антибіотик неоміцин інгібує безфакторну трансляцію полі (dТ) на стадії транслокації і не впливає на взаємодію Phe-тPHKᴾʰᵉ з полі (U)-програмованими рибосомами (зв’язування і транспептидацію). The activity of poly(U) and poly(dT) in the factor-free binding of Phe-tRNAᴾʰᵉ to the E. coli 70S ribosomes has been compared to study the role of the codon sugar-phosphate backbone in the mRNA decoding process. Poly(dT) is shown to be effectively translated in such a factor-free system at both low (2 °C) and high (37 °C) temperatures. Under the same conditions poly(U) is not translated. Neomycin inhibits factor-free poly(dT) translation and has no effect on the binding of Phe-tRNAphe to poly(U) programmed ribosomes. The data obtained indicate the great importance of the template and its sugar-phosphate backbone in the translocation process.